Numbers: britannica discovery library - Hartman, Carrie (Encyclopaedia Britannica, Inc. Chicago, 2006)
Unravel the fascinating world of numbers, exploring their significance in mathematics, science, and everyday life, while uncovering patterns and relationships that govern our universe.